Ղարաբաղի Իբրահիմ խանի սպանության հարցի շուրջ - Մաղալյան, Արտակ (Մատենադարան)
On 8 February 1806, Prince Pavel Tsitsianov, Commander of the Russian troops in the Caucasus, was assassinated in Baku. After that, riots broke out in Muslim- inhabited regions of the South Caucasus. Taking advantage of the chaos, the Persian army led by Crown Prince Abbas-Mirza started advancing towards the borders of Karabakh. When the Persian army crossed the Araxes and approached Shushi, Ibrahimkhan of Karabakh moved his family from Shushi to a place called “sangyar (fortification) of Mirza-Ali-bek” located some 4 miles away from the Shushi fortress. At night on 27 May 1806, while attempting to join the Persian army, Ibrahimkhan of Karabakh was killed by the Russian army Major D. T. Lisanevich, who had been informed about Ibrahim’s treacherous intentions from Melik Jumshud Melik- Shahnazaryan of Varanda. Our analysis of the available facts leads to an unambiguous conclusion that Ibrahim- khan was going to betray the Russian Empire and join the Persian army advancing towards Shushi; that is why he was killed by Major Lisanevich. As the Commander of the Russian troops located in Shushi, Major Lisanevich acted in line with the actual explosive situation; otherwise, in the event of his inaction or delay, he would expose himself and his subordinate soldiers to a serious danger. As to Melik Jumshud, who informed Major Lisanevich about Ibrahim-khan’s treacherous intentions, his actions were compelled by the tragedy of the Melikdoms of Khamsa (the union of the five Armenian Principalities of Artsakh-Karabakh) and the bitter lessons that made him distrust Ibrahim-khan. После убийства в Баку главнокомандующего русскими войсками на Кавказе князя Павла Цицианова 8 февраля 1806 года, в районах Закавказья, насе ленных мусульманами, начались беспорядки. Воспользовавшись возникшим хаосом, персидские войска во главе с наследником престола Аббас-Мирзой начали продвижение к границам Карабаха. Когда персидская армия, перейдя Аракс, приблизилась к Шуши, карабахский Ибрагим-хан переселил свою семью из Шуши в местность под названием “сангяр (укрепление) Мирзы-Али- бека”, находящуюся в четырех верстах от Шушинской крепости. Ночью 27 мая 1806 года, во время попытки присоединения к персидским войскам, Ибрагим-хан был убит майором русской армии Д. Лисаневичем. О предательском намерении Ибрагим-хана Лисаневичу сообщил варандинский Мелик-Джумшуд Мелик-Шахназарян. Анализ имеющихся фактов приводит к однозначному выводу о том, что Ибрагим-хан собирался изменить Российскому государству и присоединиться к персидским войскам, наступавшим на Шуши, за что и был убит майором Лисаневичем. Как командующий российскими войсками, расквартированными в Шуши, майор Лисаневич действовал в соответствии с создавшейся взрывоопасной си- туацией, поскольку в случае бездействия или промедления мог бы создать опасность для себя и подчиненных себе солдат. Что касается Мелика-Джумшуда, уведомившего майора Лисаневича о предательском намерении Ибрагим-хана,– этот шаг был продиктован трагедией Меликств Хамсы (союза пяти армянских княжеств Арцаха) и горькими уроками, которые извлек мелик, имевший все основания не доверять Ибрагим-хану.
Keywords: Պատմություն